Environmental policies and media reporting in Pakistan / Nisar A. Zuberi - Zuberi, Nisar A. (Faculty of Communication and Media Studies (FCMS), 1993)
Pakistan is yet another county where consciousness about the environment came late and where numerous problems impede the rapid adjustment needed for hazard-free surroundings. The major being the effective implementation of the policies adopted so far, Pakistan is confronted with dangers of environmental degradation and depletion of resources on one hand and the growth of population with the rate of 3.01 per cent on the other. Being the ninth most populous country in the world, Pakistan has been able to sustain more than four fold increase in population during this century. How the expected 143 million will be living here by the year 2000 is not totally unimaginable as the catastrophic signs have already begun to cast their shadows. The official national Report (NATREP) which has been prepared for the coming UN Conference on Environment and Development (UNCED), says the country faces the specific problems of high population growth, low literacy, widespread poverty, urbanisation and environmentally hostile industrialization only (Muhammad Ilyas, 1991). Many would challenge this instance with the view that environmental degradation is growing on because available legislations and rules are not being implemented.